1987
DOI: 10.1016/s0022-5347(17)42999-5
|View full text |Cite
|
Sign up to set email alerts
|

Epididymitis: Aspects Concerning Etiology and Treatment

Abstract: Extended microbiological studies were performed on 49 patients with acute or chronic epididymitis, including bacteriology of epididymal specimens in cases of scrotal surgery. In no patient had instrumentation or catheterization resulted in epididymitis. The microbiological data showed a prevalence of Chlamydia trachomatis epididymal infections in men less than 40 years old, whereas common urinary tract pathogens prevailed in older patients. Cultures of urethral swabs and midstream urine provided reliable infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 10 publications
3
31
0
4
Order By: Relevance
“…Our data showed that pyuria correlated with fever (p=0.0159). In contrast to younger men, in whom sexually transmitted pathogens are predominant, in older patients with a history of subvesical obstruction, E. coli is the most frequent pathogen responsible [16]. These data support our data mentioned above and overcome the limited evidence for not only etiology but also treatments, especially in older patients.…”
Section: Discussionsupporting
confidence: 89%
“…Our data showed that pyuria correlated with fever (p=0.0159). In contrast to younger men, in whom sexually transmitted pathogens are predominant, in older patients with a history of subvesical obstruction, E. coli is the most frequent pathogen responsible [16]. These data support our data mentioned above and overcome the limited evidence for not only etiology but also treatments, especially in older patients.…”
Section: Discussionsupporting
confidence: 89%
“…have presented that in men younger than 40 years old, 56% of epididymitis cases were caused by Chlamydia trachomatis and 18% by other bacteria. Whereas in those older than 40 years, the incidence of epididymitis resulting from urinary tract infection bacteria was 68% and only 18% from C. trachomatis [3]. The similar proportion was noted by De Jong Z. et al In a group of 12 patients older than 35 yrs., 10 pts.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to younger men where sexually transmitted pathogens are predominant, in older patients with a history of subvesical obstruction, E. coli is the most frequent pathogen responsible [2,3]. Immediate sequelae such as abscess formation are estimated to require surgical treatment in ª 10% [3,7] to 20% [6], depending on the antimicrobial agent used for therapy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Epididymitis normally results from canalicular bacterial infection of the epididymis. Escherichia coli is the predominant pathogen in men over 35 years of age with infravesical obstruction [2,3]. One severe complication of acute epididymitis is impaired fertility, even when clinically the disease is unilateral [4,5].…”
Section: Introductionmentioning
confidence: 99%